Mechanochemical synthesis of antifungal bis(benzoxaboroles). Issue 61 (7th October 2020) - Borys, Krzysztof M.; Wieczorek, Dorota; Tarkowska, Magdalena; Jankowska, Agnieszka; Lipok, Jacek; Adamczyk-Woźniak, Agnieszka
Abstract : Several piperazine bis(benzoxaboroles) have been obtained mechanochemically – two of them have been shown to display high antifungal activity. Abstract : Several piperazine bis(benzoxaboroles) have been obtained both in solution as well as in the solid state. The environmentally friendly mechanochemical approach – hitherto not applied for the preparation of benzoxaboroles – was particularly beneficial in the case of two products afforded in low yields in solution. The in vitro studies showed high potential of the studied bis(fluorobenzoxaboroles) as antifungal agents, highlighting also the influence of the fluorine substituent position on their microbiological activity. The highest activity against A. niger, A. terreus, P. ochrochloron, C. tenuis and C. albicans was displayed by the analogue of the known benzoxaborole antifungal drug Kerydin® (Tavaborole).